Mirror image agnosia - Sadanandavalli Retnaswami Chandra (Indian Journal of Psychological Medicine, 2014)
Background: Gnosis is a modality-specific ability to access semantic knowledge of an object or stimulus in the presence of normal perception. Failure of this is agnosia or disorder of recognition. It can be highly selective within a mode. self-images are different from others as none has seen one′s own image except in reflection. Failure to recognize this image can be labeled as mirror image agnosia or Prosopagnosia for reflected self-image. Whereas mirror agnosia is a well-recognized situation where the person while looking at reflected images of other objects in the mirror he imagines that the objects are in fact inside the mirror and not outside. Material and Methods:: Five patients, four females, and one male presented with failure to recognize reflected self-image, resulting in patients conversing with the image as a friend, fighting because the person in mirror is wearing her nose stud, suspecting the reflected self-image to be an intruder; but did not have prosopagnosia for others faces, non living objects on self and also apraxias except dressing apraxia in one patient. This phenomena is new to our knowledge. Results: Mirror image agnosia is an unique phenomena which is seen in patients with parietal lobe atrophy without specificity to a category of dementing illness and seems to disappear as disease advances. Discussion: Reflected self-images probably have a specific neural substrate that gets affected very early in posterior dementias specially the ones which predominantly affect the right side. At that phase most patients are mistaken as suffering from psychiatric disorder as cognition is moderately preserved. As disease becomes more widespread this symptom becomes masked. A high degree of suspicion and proper assessment might help physicians to recognize the organic cause of the symptom so that early therapeutic interventions can be initiated. Further assessment of the symptom with FMRI and PET scan is likely to solve the mystery of how brain handles reflected self-images. Conclusion: A new observation involving failure to recognize reflected self-images is reported.